2023
DOI: 10.3390/ani13081416
|View full text |Cite
|
Sign up to set email alerts
|

A Diet Rich in HUFAs Enhances the Energetic and Immune Response Capacities of Larvae of the Scallop Argopecten purpuratus

Abstract: Massive mortalities in farmed larvae of the scallop Argopecten purpuratus have been associated with pathogenic Vibrio outbreaks. An energetic trade-off between development-associated demands and immune capacity has been observed. Given that highly unsaturated fatty acids (HUFAs) are essential nutrients for larval development, we evaluated the effect of diets based on microalgae low and high in HUFAs (LH and HH, respectively) on the energetic condition and the immune response of scallop larvae. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
0
0
Order By: Relevance
“…Even an increase in oocyte diameter can imply an increase in yolk content [19]. Therefore, the larger oocyte size observed in the natural state is associated with a high accumulation of energy reserves, especially lipids [38,43,46,47], such as polyunsaturated fatty acids (HUFA), which are part of the matrix and cell membranes [10,48]. In this study, significant differences were found in the lipid content of the oocytes with values of 98.9 ± 8.3 mg g −1 dry mass and 41.6 ± 6.7 mg g −1 dry mass in the natural (environment) and (hatchery) conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even an increase in oocyte diameter can imply an increase in yolk content [19]. Therefore, the larger oocyte size observed in the natural state is associated with a high accumulation of energy reserves, especially lipids [38,43,46,47], such as polyunsaturated fatty acids (HUFA), which are part of the matrix and cell membranes [10,48]. In this study, significant differences were found in the lipid content of the oocytes with values of 98.9 ± 8.3 mg g −1 dry mass and 41.6 ± 6.7 mg g −1 dry mass in the natural (environment) and (hatchery) conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%